Interactive storytelling with haptic interaction for mobile / Muhammad Fadzly Mohammed Shamsi - Mohammed Shamsi, Muhammad Fadzly (2014)
The interactive storytelling has become an instructional and learning tool for children and students. This research paper identifies a summary of interactive storytelling. To analyze the better interactive storytelling, this research described how the storytelling which combined with haptic interaction for mobile can be used to support instruction process and how users can have their interaction with the application by using haptic interaction for mobile approach. In addition, the content presented is about the Sunnah of Prophet Muhammad S.A.W. that can be used to improve quality of human life. The research paper also accomplishes with an overview that has been and needs to be conducted on the appreciation of Sunnah in human daily life.